2019
DOI: 10.7759/cureus.4101
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Burnout and its Factors Among Doctors Using the Abbreviated Maslach Burnout Inventory

Abstract: Background Occupational burnout is an unwanted outcome of chronic workplace stressors which may be emotional or interpersonal. Chronic exposure to human suffering and long working hours have contributed to greater job stress and early burnout among healthcare providers. This study utilized the abbreviated Maslach Burnout Inventory (aMBI) to gauge the extent of overall burnout and on three subscales – perspective taking, compassionate care, and walking in patients' shoes – among interns, postgraduate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
27
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 17 publications
4
27
0
5
Order By: Relevance
“…In questioning of the internal consistency of the MBI, depersonalization has been found to have lower reliability than the other two subscales. This finding has been consistent across both the original version and translated versions of the MBI [11]. Different alterations to the tool have often been made by changing the number of factors or items.…”
Section: Introductionsupporting
confidence: 64%
See 1 more Smart Citation
“…In questioning of the internal consistency of the MBI, depersonalization has been found to have lower reliability than the other two subscales. This finding has been consistent across both the original version and translated versions of the MBI [11]. Different alterations to the tool have often been made by changing the number of factors or items.…”
Section: Introductionsupporting
confidence: 64%
“…Despite these efforts, however, the results obtained by these versions were not conclusive enough to justify reconstructing the original tool [3]. The 3 dimensions of burnout were previously considered to be independent in their functioning based on Maslach's interpretation, but recent studies have indicated a contradicting view, as the dimensions appear to correlate with one another, with correlations up to 0.73 between depersonalization and emotional exhaustion, 0.49 between personal accomplishment and emotional exhaustion, and 0.62 between depersonalization and personal accomplishment [11]. According to several studies, personal accomplishment is observed to be the subscale that shows the weakest association with the other dimensions.…”
Section: Introductionmentioning
confidence: 95%
“…The global prevalence of burnout among postgraduate doctors is shown vary from 27 to 75% [46] . It is associated with multiple stressors in the personal and family life [4, 711], work life [6, 8, 1216], as well as factors related to their education, training and the learning environment [10, 15]. Burnout compromises postgraduate doctors’ quality of life, productivity, performance, ability to acquire knowledge and their satisfaction regarding the training programme [17, 18].…”
Section: Introductionmentioning
confidence: 99%
“…As described by Shaikh et al, 12 we combined the scores of EE and DP to calculate the overall burnout score. For EE and DP, subscale score of 0 to 9 was regarded as “no-to-low burnout” and subscale score of 10 to 18 was regarded as “moderate-to-severe burnout.” It was opposite for PA because higher PA scores indicate lesser burnout.…”
Section: Methodsmentioning
confidence: 99%